EXPERIMENTAL WORK FOR MECHANICAL PROPERTIES OF COLD-ROLLED ST-37 STEEL AT HIGH STRAIN RATES BY CONSIDERING THE MECHANICAL ANISOTROPY EFFECT - Eka Perkasa, Rilis
Cold rolling is a metal forming process which reduces the thickness of a workpiece by applying compressive force through a set of rolls below the recrystallization temperature. Unlike hot rolling process, cold rolling process produce material with higher strength, higher hardness, and anisotropy as well due to grain elongation and preferred crystallographic orientation after the plastic deformation. This research presents the study of metal anisotropy effect on mechanical properties of St-37 mild steel at high strain rates. The experiment were conducted at a quasi-static condition and at a strain rate of 1200 and 2000 s-1 by using Split Hopkinson Pressure Bar (SHPB). The specimens were prepared from unrolled and rolled (with 33.3% reduction) St-37 mild steel plate in the orientations of 00, 450, and 900 relative to the rolling direction. From the experiments, material models at the three directions were constructed using the Simplified Johnson-Cook model. The results show that the anisotropy of yield strength are more pronounced on the rolled specimens, where the specimens with the orientation perpendicular to the rolling direction consistently show the highest strength. Specimens from rolled plate also exhibit less strain rate sensitivity compared to the unrolled specimens. Numerical simulation results for non rolled specimens showed good agreement with the experimental result, while there are disagreements on strain hardening factor on rolled specimens.